MIKROTIK SOHO (Small Office Home Office) NETWORK WORKSHOP - wawan nurmansyah; Achmad Alfian; Meylinda Mulyati; Klaudius Jevanda (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2021)
Schools are generally used as places for formal community education, schools continue to evolve in terms of infrastructure development, human resources, especially teachers, and a curriculum system to keep up with the evolving times. Vocational High School prepares students who are ready to work, especially industries that need human resources who already have the required hard skills.Especially for the TKJ (computer network) concentration, students are given a workshop from the continuation of the socialization that had been previously held. The workshops are conducted online using video conferencing with the google meet application, applications such as power points and other application simulators are displayed by sharing the desktop view with workshop participants (students of SMK Xaverius 1 Palembang)Indicators for the assessment of workshop activities using a questionnaire and the results of several question points responded to by 22 students of SMK Xaverius Palembang. The highest percentage of questions "is the topic of activity interesting?" is at the 4th rate with a performance of 22.7%, the question "Material / material activity fading?" found at rate 5 with an achievement of 54.5%, the question "The delivery of the material / material is clear?" found at the 4th rate with a gain of 50%, the question "Is this activity generally interesting?" is at the 4th rate with a achievement of 54.5% and the question "Is this activity very useful?" there is the 5th rate with an achievement of 59.1%, with these results many of them have a positive attitude in this PkM activity.